Hollywood and the culture elite how the movies became American - Decherney, Peter (Film and culture, 2005)
Explores how Hollywood and cultural institutions worked together, amid ethnic diversity, the rise of mass entertainment, world war, and the global spread of American culture, to insure their own survival and profitability and to provide a coherent, though shifting, American identity.